2018
DOI: 10.20944/preprints201809.0318.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physicochemical Characterization of FRET-labelled Chitosan Nanocapsules and Model Degradation Studies

Abstract: Sub-micron o/w emulsions coated with chitosan have been used for drug delivery, quorum sensing inhibition and vaccine development. To study interactions with biological systems, nanocapsules have been fluorescently labelled in previous works, but it is often difficult to distinguish the released label from intact nanocapsules. In this study, we present advanced labelling strategies based on FRET measurements for chitosan-coated nanocapsules and investigate their dissolution and degradation. We used FRET measur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Moreover, reduced cellular binding of negatively charged nanoemulsions (diameter = 135 ± 28 nm, ζ -potential = − 31.4 ± 4.83 mV, Fig. 6 b 25 , 26 ) further confirmed that the interaction between Chi-NCs and the urothelial cells is driven by electrostatic forces (Fig. 6 b).…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…Moreover, reduced cellular binding of negatively charged nanoemulsions (diameter = 135 ± 28 nm, ζ -potential = − 31.4 ± 4.83 mV, Fig. 6 b 25 , 26 ) further confirmed that the interaction between Chi-NCs and the urothelial cells is driven by electrostatic forces (Fig. 6 b).…”
Section: Resultssupporting
confidence: 56%
“…Chi-NCs were prepared according to the solvent displacement technique 61 with modifications 26 . Briefly, an organic phase was formed by dissolving 40 mg of lecithin (Cargill, Krefeld, Germany) in 1 mL of ethanol, followed by the addition of 530 µL capsaicin solution (Sigma-Aldrich; 96% pure dissolved in ethanol to 24 mg mL −1 ), 125 μL Miglyol 812 (Peter Cremer Oleo, Hamburg, Germany), and the lipophilic dye DiO (Santa Cruz Biotechnology, Heidelberg, Germany) to obtain capsaicin concentration of 10 mM and dye concentrations of 0.158 mM, in the final formulation after evaporation 25 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations